2019
DOI: 10.3390/rs11151815
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Land Cover Mapping Based on the Convolutional Neural Network

Abstract: Super-resolution mapping (SRM) is used to obtain fine-scale land cover maps from coarse remote sensing images. Spatial attraction, geostatistics, and using prior geographic information are conventional approaches used to derive fine-scale land cover maps. As the convolutional neural network (CNN) has been shown to be effective in capturing the spatial characteristics of geographic objects and extrapolating calibrated methods to other study areas, it may be a useful approach to overcome limitations of current S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…With the rapid development of cities and the expanding population, food security has increasingly become an issue of widespread concern. As an important aspect of land-use and land-cover mapping, crop mapping also plays an important role in watershed modeling, as well as crop modeling [1][2][3]. Gathering cropland information can help us to identify the crucial problems we are facing, such as the shrinkage of cropland area caused by urban sprawl, groundwater overdraft due to cropland irrigation, and land degradation due to over-reclamation [4].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of cities and the expanding population, food security has increasingly become an issue of widespread concern. As an important aspect of land-use and land-cover mapping, crop mapping also plays an important role in watershed modeling, as well as crop modeling [1][2][3]. Gathering cropland information can help us to identify the crucial problems we are facing, such as the shrinkage of cropland area caused by urban sprawl, groundwater overdraft due to cropland irrigation, and land degradation due to over-reclamation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Not only to enhance the spatial resolution of aerial images, but the super-resolution technique can also be applied to enhance the spatial resolution of land cover maps. Jia et al (2019) showed that CNN can predict a finer land cover map given a coarse remote sensing image.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in these methods, first, the relationship between an image with a fine spatial resolution and the corresponding image with a coarse spatial resolution is established through the training process with a large amount of training data, and then the trained model is used to super-resolve the testing coarse-spatial-resolution image. These methods have been successfully applied to the SR of sea surface temperature (SST) imagery (Ping et al, 2021) and SR mapping of land cover Jia et al, 2019). Therefore, the CNN-based SR methods have great potential in the field of image downscaling, especially fine-spatial-resolution IST images and lead maps that are useful in THF estimation.…”
Section: Introductionmentioning
confidence: 99%